Craniomedial pedicled mammaplasty based on Würinger’s horizontal septum - Ryssel, Henning; Germann, Günter; Reichenberger, R. (Aesthetic plastic surgery, 2010)
During 30 months, 40 “septum-based” mammaplasties with a craniomedial pedicle were performed. This report aims to demonstrate the anatomic basics of the horizontal septum and the authors’ experience with the septum-based mammaplasty technique.
Gesehen am 28.06.2023